Using Stormwater Hysteresis to Characterize Karst Spring Discharge. Issue 4 (13th September 2012) - Toran, Laura; Reisch, Chad E.
<x xml:space="preserve">Abstract</x> Discharge from karst springs contains a mixture of conduit and matrix water, but the variations in groundwater mixing are poorly known. Storm events present an opportunity to try to map flow components because water entering during storms is more dilute and provides a tracer as it mixes with pre‐event water along the flowpath from the recharge area to discharge at a spring. We used hysteresis plots of Mg/Ca ratios in a spring in the Cumberland Valley of Pennsylvania to map conduit (higher Ca) vs. diffuse (higher Mg) sources of recharge. We observed two types of temporal heterogeneity: within a storm event and from storm to storm. The timing of the variation in Mg/Ca suggested sources of mixing waters. An increase in the Mg/Ca ratio at the beginning of some storms while conductivity declined suggested diffuse recharge through the epikarst. The rapid changes in Mg/Ca ratios for low‐intensity events probably occurred as the rainfall waxed and waned and illustrate that a variety of flowpaths are available at this spring because additional flushing of Mg occurred. In contrast, the conductivity hysteresis began with dilute water initially and rotation was similar from storm to storm. Hysteresis plots of the Mg/Ca ratio have the potential of revealing more of the complexity in discharge than conductivity alone. A better understanding of flow components in karst is needed to protect these aquifers as a groundwater resource.